New Oxford American dictionary. - Stevenson, Angus; Lindberg, Christine A., 1954- (Oxford ; New York : Oxford University Press, 2010)
From the Publisher: As Oxford's flagship American dictionary, the New Oxford American Dictionary sets the standard of excellence for lexicography in this country. With more than 350,000 words, phrases, and senses, hundreds of explanatory notes, and more than a thousand illustrations, this dictionary provides the most comprehensive and accurate coverage of American English available. The dictionary draws on the two-billion-word Oxford English Corpus and the unrivaled citation files of the world-renowned Oxford English Dictionary to provide the most accurate and richly descriptive picture of American English ever offered in any dictionary. The Third Edition offers a thoroughly updated text, with revisions throughout and approximately 2,000 new words, phrases, and meanings. Many new words relate to fast-moving areas such as computing, technology, current affairs, and ecology, while others have recently entered the popular lexicon. Usage notes have been updated in light of the most recent Corpus evidence, and a completely new in-text feature on Word Trends charts usage for rapidly changing words and phrases such as carbon, mobile, or tweet. In addition, the volume has an attractive, modern new text design that makes entries easier to read and find. One of the hallmarks of the New Oxford American Dictionary is the way it reflects the living language. Unlike in more traditional dictionaries, where meanings are ordered chronologically according to the history of the language, each entry plainly shows the principal meaning or meanings of the word, organized by importance in today's English. Thus readers can be confident that the first definition they see is the one most likely to be used by people today, and is not a sense that has been obsolete for two centuries. Offering clear, authoritative, and precise information, with the in-depth and up-to-date coverage that users need and expect, the New Oxford American Dictionary is the benchmark by which all other American dictionaries are measured.
Editorial staff -- Advisory board -- Specialist subject consultants -- Preface -- Preface to the first edition -- Introduction -- How to use this dictionary -- Key to pronunciations -- Key to abbreviations -- New Oxford American dictionary -- Ready reference -- Illustrations credits.
Revised ed of: New Oxford American dictionary / Elizabeth J. Jewell, Frank Abate, 1st ed.
Keywords: English language -- United States -- Dictionaries; Americanisms -- Dictionaries